Making Green(s) With Black and White: Constructing Soils for Urban Agriculture Using Earthworms, Organic and Mineral Wastes - Araujo, J. H. R.; Pando-Bahuon, A.; Hartmann, C.; Aroui-Boukbida, H.; Desjardins, T.; Lerch, Thomas Z. (Frontiers in Ecology and Evolution, 2022)
Urban agriculture has been of growing interest for a decade because it can address many economic and societal issues in the development of modern cities. However, urban agriculture is often limited by the availability of fertile and non-contaminated soils in the cities. Recycling excavated mineral wastes from building activities to construct fertile soils may be a more sustainable alternative than the importation of topsoils from rural zones. The present study aims to evaluate the possibility to grow green vegetables on soils made with excavated deep horizon of soils and green waste compost. During three consecutive seasons, we tested in situ the effects of different amounts of compost (10%, 20% and 30%) and the presence of an earthworm species (Lumbricus terrestris) on the production of lettuce, arugula and spinach in mono- and co-cultures. Our results demonstrate that it is possible to reuse mineral and organic urban wastes to engineer soils adapted to agriculture. Here, we observed that the higher doses of compost significantly increase plant biomass, especially when earthworms were introduced. These results were partly due to the positive effects of these two factors on soil physical properties (porosity). This preliminary study also showed that some plants (arugula) are more adapted than others (lettuce) to the soil properties and that it only takes few months to get the highest yields. These promising results for urban agriculture obtained by a soil engineering approach suggest to test the growth of other plants and carry experiments on longer-term periods.